IMPLICATION OF OPEN SYNTAX ON DERIVED ADJECTIVES - Fisayo Andrew , Ajala; Chidinma Priscilla, Onyemakonor (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Adjectivization is a transformational process of converting a lexical item in a language into an adjectival form. This paper reviews previous word formation processes attested for creating new adjectives in Yoruba and examines the syntactic idiosyncrasies of the derived adjectives when used in open syntax. The data employed in this study is gathered from a variety of sources, including several settings and environments in which the native speakers use the Yoruba language freely. Published and unpublished works that are also related to the research were consulted. The framework for the study was based on Dixon’s (1997) Basic Linguistic Theory because of its descriptive adequacy and flexibility rather than trying to force the language into a model based on European languages. The research, amongst others, reveals that the derived adjectives with the inherent [+be] do not need the Yoruba copula verb ‘ń́i’ which most derived adjectives require to make sense. The work also reveals that the adjective so derived are not only lexical structures but also post lexical structures